Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the matrix equation [tex]\( A X + B = C \)[/tex] for [tex]\( X \)[/tex].
Given matrices:
[tex]\[ A = \begin{pmatrix} -3 & -4 \\ 1 & 0 \end{pmatrix}, \quad B = \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix}, \quad C = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} \][/tex]
We need to isolate [tex]\( X \)[/tex]. First, we rearrange the equation:
[tex]\[ A X + B = C \][/tex]
[tex]\[ A X = C - B \][/tex]
[tex]\[ X = A^{-1} (C - B) \][/tex]
### Step 1: Calculate [tex]\( C - B \)[/tex]
[tex]\[ C - B = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} - \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix} = \begin{pmatrix} -42 - (-7) & -20 - (-9) \\ 5 - 4 & 4 - (-1) \end{pmatrix} \][/tex]
[tex]\[ C - B = \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
### Step 2: Calculate the inverse of matrix [tex]\( A \)[/tex]
The inverse of a [tex]\( 2 \times 2 \)[/tex] matrix [tex]\( A = \begin{pmatrix} a & b \\ c & d \end{pmatrix} \)[/tex] is given by:
[tex]\[ A^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For matrix [tex]\( A \)[/tex]:
[tex]\[ A = \begin{pmatrix} -3 & -4 \\ 1 & 0 \end{pmatrix} \][/tex]
Let's calculate the determinant [tex]\( \text{det}(A) \)[/tex]:
[tex]\[ \text{det}(A) = (-3 \times 0) - (1 \times -4) = 0 + 4 = 4 \][/tex]
Since the determinant is non-zero, [tex]\( A \)[/tex] is invertible.
[tex]\[ A^{-1} = \frac{1}{4} \begin{pmatrix} 0 & 4 \\ -1 & -3 \end{pmatrix} = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \][/tex]
### Step 3: Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( C - B \)[/tex]
[tex]\[ X = A^{-1} (C - B) = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
Calculating this matrix multiplication:
[tex]\[ X_{11} = 0 \cdot (-35) + 1 \cdot 1 = 1 \][/tex]
[tex]\[ X_{12} = 0 \cdot (-11) + 1 \cdot 5 = 5 \][/tex]
[tex]\[ X_{21} = -0.25 \cdot (-35) + (-0.75) \cdot 1 = 8.75 - 0.75 = 8 \][/tex]
[tex]\[ X_{22} = -0.25 \cdot (-11) + (-0.75) \cdot 5 = 2.75 - 3.75 = -1 \][/tex]
So, the matrix [tex]\( X \)[/tex] is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Thus, the correct value of [tex]\( X \)[/tex] is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
The corresponding choice is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Given matrices:
[tex]\[ A = \begin{pmatrix} -3 & -4 \\ 1 & 0 \end{pmatrix}, \quad B = \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix}, \quad C = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} \][/tex]
We need to isolate [tex]\( X \)[/tex]. First, we rearrange the equation:
[tex]\[ A X + B = C \][/tex]
[tex]\[ A X = C - B \][/tex]
[tex]\[ X = A^{-1} (C - B) \][/tex]
### Step 1: Calculate [tex]\( C - B \)[/tex]
[tex]\[ C - B = \begin{pmatrix} -42 & -20 \\ 5 & 4 \end{pmatrix} - \begin{pmatrix} -7 & -9 \\ 4 & -1 \end{pmatrix} = \begin{pmatrix} -42 - (-7) & -20 - (-9) \\ 5 - 4 & 4 - (-1) \end{pmatrix} \][/tex]
[tex]\[ C - B = \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
### Step 2: Calculate the inverse of matrix [tex]\( A \)[/tex]
The inverse of a [tex]\( 2 \times 2 \)[/tex] matrix [tex]\( A = \begin{pmatrix} a & b \\ c & d \end{pmatrix} \)[/tex] is given by:
[tex]\[ A^{-1} = \frac{1}{ad - bc} \begin{pmatrix} d & -b \\ -c & a \end{pmatrix} \][/tex]
For matrix [tex]\( A \)[/tex]:
[tex]\[ A = \begin{pmatrix} -3 & -4 \\ 1 & 0 \end{pmatrix} \][/tex]
Let's calculate the determinant [tex]\( \text{det}(A) \)[/tex]:
[tex]\[ \text{det}(A) = (-3 \times 0) - (1 \times -4) = 0 + 4 = 4 \][/tex]
Since the determinant is non-zero, [tex]\( A \)[/tex] is invertible.
[tex]\[ A^{-1} = \frac{1}{4} \begin{pmatrix} 0 & 4 \\ -1 & -3 \end{pmatrix} = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \][/tex]
### Step 3: Multiply [tex]\( A^{-1} \)[/tex] by [tex]\( C - B \)[/tex]
[tex]\[ X = A^{-1} (C - B) = \begin{pmatrix} 0 & 1 \\ -0.25 & -0.75 \end{pmatrix} \begin{pmatrix} -35 & -11 \\ 1 & 5 \end{pmatrix} \][/tex]
Calculating this matrix multiplication:
[tex]\[ X_{11} = 0 \cdot (-35) + 1 \cdot 1 = 1 \][/tex]
[tex]\[ X_{12} = 0 \cdot (-11) + 1 \cdot 5 = 5 \][/tex]
[tex]\[ X_{21} = -0.25 \cdot (-35) + (-0.75) \cdot 1 = 8.75 - 0.75 = 8 \][/tex]
[tex]\[ X_{22} = -0.25 \cdot (-11) + (-0.75) \cdot 5 = 2.75 - 3.75 = -1 \][/tex]
So, the matrix [tex]\( X \)[/tex] is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Thus, the correct value of [tex]\( X \)[/tex] is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
The corresponding choice is:
[tex]\[ X = \begin{pmatrix} 1 & 5 \\ 8 & -1 \end{pmatrix} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.